Correlation of Salivary Glucose Level with Blood Glucose Level in Diabetes Mellitus - Arati S. Panchbhai (Stilus Optimus, 2012)
Objectives: There is alarming rise in number of people with diabetes mellitus over these years. If glucose in saliva is linked to glucose in blood it can be used to detect diabetes mellitus at an early stage. The present study is undertaken with the aim to assess the correlation of salivary glucose level with blood glucose level in people with diabetes mellitus. Material and Methods: For investigations, 2 sets of samples of people with diabetes and the age and sex matched non-diabetic subjects were recruited. The salivary glucose was analyzed in unstimulated whole saliva samples using glucose oxidase method. Pearson's correlation coefficient test was applied to assess the correlation between salivary glucose level and blood glucose level. Results: The significant (P < 0.05) positive correlation of salivary glucose level and fasting blood glucose level was observed in people with uncontrolled diabetes in both the sets of samples.Conclusions: Although study suggests some potential for saliva as a marker in monitoring of diabetes mellitus, there are many aspects that need clarification before we reach to a conclusion.